2018
DOI: 10.1016/j.jor.2018.08.016
|View full text |Cite|
|
Sign up to set email alerts
|

Postoperative hemoglobin and recovery of hip muscle strength after total hip arthroplasty

Abstract: We need to consider perioperative strategies to minimize anemia in order to improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Moreover, there are fewer female smokers than male smokers, which may also explain why women are more likely to develop PONV than men. Perioperative anemia is common in orthopedic patients and is associated with adverse clinical outcome (17). Similarly, in our study, patients with low preoperative Hb levels were more likely to develop PONV from the result in 6-24 hours and 24-72 hours.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, there are fewer female smokers than male smokers, which may also explain why women are more likely to develop PONV than men. Perioperative anemia is common in orthopedic patients and is associated with adverse clinical outcome (17). Similarly, in our study, patients with low preoperative Hb levels were more likely to develop PONV from the result in 6-24 hours and 24-72 hours.…”
Section: Discussionsupporting
confidence: 77%
“…A similar study on 122 THAs in patients >65 years of age demonstrated a correlation between postoperative Hb and recovery in the 6-minute walking test 51 . Furthermore, a study of 82 THAs showed better recovery of hip muscle strength in patients with a postoperative:preoperative Hb ratio of >0.85 on POD10 52 . In our study, 22.7% of patients in the wax group had a postoperative:preoperative Hb ratio of <0.85 on POD5, compared with 53.2% of those in the control group; this difference was significant and might imply better recovery of hip muscles in the wax group.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies had indicated that hypoalbuminemia was associated with increased short-term mortality and complications 13 [14,21]. Perioperative anemia was associated with signi cant adverse clinical outcomes, such as decreased physical function [22], increased transfusions [23], complications and mortality [24,25]. These results indicated that the drop of albumin was a predictor for adverse postoperative outcomes in the elderly patients with FNF undergoing hip arthroplasty.…”
Section: Discussionmentioning
confidence: 97%